Prognostic factors in canine acute leukaemias: a retrospective study. (26th January 2015) - Novacco, M.; Comazzi, S.; Marconato, L.; Cozzi, M.; Stefanello, D.; Aresu, L.; Martini, V.
Abstract: Canine acute leukaemias (ALs) have a poor prognosis, with reported survival times (ST) of only a few weeks or months. Also, clinical studies assessing prognostic factors are lacking. This study aims to retrospectively assess variables that predict ST in dogs with AL, and to identify correlations between outcome and therapeutic protocols. Diagnosis and sub‐classification into AL subtypes was made based on haematological findings, morphological assessment and flow cytometric immunophenotyping. Clinical–pathological features of AL subtypes at presentation concurred with those described in the literature. A normal neutrophil count at presentation significantly prolonged ST ( P  = 0.027). Additionally, there was a trend for anaemic dogs to have shorter survival compared with those without anaemia, and the incorporation of cytosine in the chemotherapy protocol produced a moderate but not significant increase in median ST for dogs with AL. Further prospective studies with standardized treatments are needed to confirm and improve our results.